Insights Into the Complexity of Yeast Extract Peptides and Their Utilization by Streptococcus thermophilus - Proust, Lucas; Sourabié, Alain; Pedersen, Martin; Besançon, Iris; Haudebourg, Eloi; Monnet, Véronique; Juillard, Vincent (Frontiers in Microbiology, 2019)
Streptococcus thermophilus, an extensively used lactic starter, is generally produced in yeast extract-based media containing a complex mixture of peptides whose exact composition remains elusive. In this work, we aimed at investigating the peptide content of a commercial yeast extract (YE) and identifying dynamics of peptide utilization during the growth of the industrial S. thermophilus N4L strain, cultivated in 1-liter bioreactors under pH-regulation. To reach that goal, we set up a complete analytical workflow based on mass spectrometry (peptidomics). About 4,600 different oligopeptides ranging from 4 to more than 30 amino acids in length were identified during the time-course of the experiment. Due to the low spectral abundance of individual peptides, we performed a clustering approach to decipher the rules of peptide utilization during fermentation. The physicochemical characteristics of consumed peptides perfectly matched the known affinities of the oligopeptide transport system of S. thermophilus. Moreover, by analyzing such a large number of peptides, we were able to establish that peptide net charge is the major factor for oligopeptide transport in S. thermophilus N4L.